The electrocardiographic T wave changes in highly trained athletes during training. An old problem revisited - Spataro, A.; La Mura, G; Marcello, G.; Alabiso, A.; Naccari, D.; Pelliccia, A. (The Journal of Sports Medicine and Physical Fitness, 1998)
OBJECTIVE: To evaluate the T-wave pattern alterations during vigorous training in elite athletes. SETTING: Institute of Sport Science in Rome and National Rowing Center in Piediluco, Italy. STUDY POPULATION: Nine male and 7 female rowers of the national team were examined prospectively at different times of their conditioning period. METHODS: All athletes underwent electrocardiography and echocardiography; the ecg was analyzed for QRS voltages and axis, T-wave pattern and QTc interval; from echocardiography the left ventricular (LV) cavity dimension, wall thickness and mass were calculated. From Doppler-echocardiography the transmitral diastolic LV filling pattern was evaluated. RESULTS: Variation of T-wave voltages was seen in all the athletes. Specifically, during the low-intensity training period the T-wave pattern was positive and increased in voltage (T-wave max amplitude in V6 increased to 130% in male and 100% in female than pretraining values). During the peak training a variety of patterns was observed, and a transient flattening was present in 50% of subjects. No concomitant alteration of heart rate, QRS and T-wave axis and QTc duration were observed. No significant changes of cavity dimension, wall thickness, LV mass index and Doppler-derived diastolic peak flow velocities were detected during the study period. CONCLUSIONS: Transient changes of T-wave pattern may occur in athletes as an effect of athletic conditioning, without changes of cardiac dimension or alteration of indexes of LV function. This finding supports the role of ecg monitoring to follow-up the individual athletes response to training exercise load.